Generalized microbundles and locally flat imbeddings - Matuzevičius, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. И. Матузявичюс. Обобщенные микропучки и локально плоские вложенияA. Matuzevičius. Apibendrinti mikroišluoksniavimai ir lokaliai plokšti įdėjimai